The Concept of Leadership in the Philosophy of Educational Management from the Perspective of the Qur'an and Hadith - Fansori , Rosihan; Wardhana , Kautsar Eka; Bighas, Khadijah A (Program Studi Pendidikan Agama Islam (PAI), 2024)
This research aims to explore the concept of leadership in the philosophy of educational management from the perspective of the Qur'an and Hadith. Leadership in this context is understood as a key role in guiding, managing, and shaping an educational environment in line with Islamic values. The research method used is a literature review of the Qur'an and Hadith, focusing on verses and hadiths related to the concept of leadership.In the context of the Qur'an, the concept of Tawhid stands out as the foundation of leadership that recognizes the oneness of God as the central point of all leader actions. Moreover, values of mercy and concern are also recognized as distinctive characteristics of effective educational leaders.The findings of this research conclude that the concept of leadership in the philosophy of educational management, when viewed from the perspective of the Qur'an and Hadith, has a strong ethical foundation. Educational leaders are expected to be responsible stewards managing educational resources in accordance with the principles of Tawhid and justice. Leadership grounded in the Qur'an and Hadith also teaches moral values, participative decision-making, and care for the development of the entire educational community.This research is expected to provide a deeper insight into the concept of leadership in the context of education management inspired by Islamic teachings. The implications of this research can contribute to a more meaningful, ethical understanding of leadership practices in line with Islamic values in the effort to improve the quality of education